Oil palm by products as feeds for livestock in Malaysia - Wan Zahari Mohamed; M. Mohd Farid (2011)
Oil palm fronds (OPF), oil palm trunks (OPT), palm press fiber (PPF), palm kernel cake (PKC) and palm oil mill effluent (POME) are the main by-products from the oil palm industry which can be used as ingredients for livestock feeding. Many of the field residues and processing mills are high fibrous materials which need further processing for better utilization in ruminant animals. OPF has been widely utilized as feedstuff either in the form of freshly chopped, silage, or processed into pellets and cubes. Optimum inclusion level in beef and dairy animals is about 30 %. Ensiled OPT produced reasonably good live-weight gain (LWG) of about 0.7 kg/day in beef cattle when fed at levels between 30 – 40 %. PPF on the other hand, has a lower digestibility, which limits its inclusion in ruminant diets to less than 20 %. PKC is a high energy source and is a cost-effective ingredient to be utilized in ration formulations for various livestock species. High content of fiber and shell can limit its utilization in poultry and aquaculture. With biotechnological treatments, inclusion levels of PKC can be increased for poultry and aquaculture feeding. Palm fatty acid distillates (PFAD) from oil palm refineries are often used for supplementing non ruminant animals and aquaculture. The experience by the CK Agrifeed Sdn Bhd in the development of complete feeds based on these products is highlighted.